Graph the inequality on the numberline and then write it in interval notation.

11z+3(z-1)≤4z-13

3 answers

Please help me solve and then graph on a numberline along with the interval notation.
11 z + 3 ( z - 1 ) ≤ 4 z -13

11 z + 3 ∙ z + 3 ∙ ( - 1 ) ≤ 4 z -13

11 z + 3 z - 3 ≤ 4 z -13

14 z - 3 ≤ 4 z -13

Subtract 4 z to both sides

14 z - 3 - 4 z ≤ 4 z -13 - 4 z

10 z - 3 ≤ -13

Add 3 to both sides

10 z - 3 + 3 ≤ -13 + 3

10 z ≤ -10

Divide both sides by 10

z ≤ -1

Interval notation:

z ∈ ( - ∞ , 1 ]
My typo.

Sorry.

z ∈ ( - ∞ , - 1 ]